An integrated bioremediation process for petroleum hydrocarbons removal and odor mitigation from contaminated marine sediment. (15th October 2015) - Zhang, Zhen; Lo, Irene M.C.; Yan, Dickson Y.S.
Abstract: This study developed a novel integrated bioremediation process for the removal of petroleum hydrocarbons and the mitigation of odor induced by reduced sulfur from contaminated marine sediment. The bioremediation process consisted of two phases. In Phase I, acetate was dosed into the sediment as co-substrate to facilitate the sulfate reduction process. Meanwhile, akaganeite (β-FeOOH) was dosed in the surface layer of the sediment to prevent S 2− release into the overlying seawater. In Phase II, NO 3 − was injected into the sediment as an electron acceptor to facilitate the denitrification process. After 20 weeks of treatment, the sequential integration of the sulfate reduction and denitrification processes led to effective biodegradation of total petroleum hydrocarbons (TPH), in which about 72% of TPH was removed. In Phase I, the release of S 2− was effectively controlled by the addition of akaganeite. The oxidation of S 2− by Fe 3+ and the precipitation of S 2− by Fe 2+ were the main mechanisms for S 2− removal. In Phase II, the injection of NO 3 − completely inhibited the sulfate reduction process. Most of residual AVS and S 0 were removed within 4 weeks after NO 3 − injection. The 16S rRNA clone library-based analysis revealed a distinct shift of bacterial community structure in the sediment over different treatment phases. The clones affiliated with Desulfobacterales and Desulfuromonadales were the most abundant in Phase I, while the clones related to Thioalkalivibrio sulfidophilus, Thiohalomonas nitratireducens and Sulfurimonas denitrificans predominated in Phase II. Graphical abstract: Highlights: A novel integrated bioremediation process was developed for TPH and odor removal. Integration of sulfate reduction and denitrification led to effective TPH removal. Nitrate was effective in removing AVS and inhibiting sulfate reduction in sediment. Oxidation and precipitation were key mechanisms for S 2− removal by akaganeite. Distinct shift of bacterial community was detected over different treatment phases.